A method for extracting collagen and aquatic animals, collagen and products containing it - Md Yusoff, Fatimah; Bakar, Jamilah; Basri, Mahiran; Ismail, Maznah; Khong, Nicholas Mun Hoe (2013)
The present invention provides an improved process for extracting collagen from aquatic animals, comprising alkaline treatment, followed by acidic treatment in combination with an orderly sequence of physical and/or mechanical treatments and precipitation of collagen using a salt solution. The process increases the yield and quality of the collagen while decreasing the production time and is more cost-effective than the processes known heretofore. The invention further includes the obtained collagen and products containing it.